Developing skills for employability with German Partners : 8 success stories from Central and Eastern European Countries and the CIS - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
"This brochure presents eight vocational education and training success stories of skill development realised in a joint effort by partners from Germany and from Central and Eastern Europe as well as the Commonwealth of Independent States (CIS). With its wide range of tranining offers and its strong emphasis on employability, 'Training - Made in Germany' has the potential to succesfully contribute to the design process of the training systems in these regions through co-operation projects." (Text extract, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.2 Europa; I 2.2.2 Osteuropa; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Mitteleuropa; Osteuropa; GUS